Dissemination and characterisation of Escherichia coli producing extended-spectrum β-lactamases, AmpC β-lactamases and metallo-β-lactamases from livestock and poultry in Northeast India: A molecular surveillance approach. (June 2019) - Tewari, Rituparna; Mitra, Susweta; Ganaie, Feroze; Das, Sangita; Chakraborty, Anamika; Venugopal, Nimita; Shome, Rajeswari; Rahman, Habibur; Shome, Bibek R.
Highlights: High prevalence of ESBL and AmpC resistance determinants among E. coli circulating in livestock and poultry in India. Nine plasmid replicon types were distributed among resistant E. coli ; multiple plasmids were observed in 28% of isolates. Virulence genes were detected in 81% of β-lactam-resistant E. coli strains, with traT and stx2 genes being predominant. Globally important ST10 and ST676 strains identified, contributing to the growing crisis of antimicrobial resistance (AMR). Need for rigorous surveillance in animal sector to identify critical control points to prevent rapid dissemination of AMR. Abstract: Objectives: The aim of this study was to identify and characterise probable extended-spectrum β-lactamase (ESBL)-, AmpC lactamase- and/or metallo-β-lactamase (MBL)-producing Escherichia coli variants circulating in the livestock and poultry environment to establish their epidemiological significance, genetic diversity, antimicrobial resistance (AMR) trends and virulence. Methods: The culture method and E. coli -specific multiplex PCR identified 78 E. coli strains from faecal samples of healthy livestock and poultry. The antibiogram was determined by the disk diffusion and minimum inhibitory concentration (MIC) methods. Antimicrobial-resistant E. coli isolates were screened for the presence of ESBL, AmpC and MBL genes. Isolates were further characterised by plasmid replicon typing, integron assay and virulence gene analysis. Genetic diversity was assessed by random amplification of polymorphic DNA (RAPD) analysis and multilocus sequence typing (MLST). Results: ESBL (CTX-M group 1, CTX-M group 4, TEM), AmpC (EBC, FOX, CMY, DHA) and MBL (IMP, SIM) resistance determinants were identified in 75%, 19% and 6% of isolates, respectively. Nine plasmid replicon types were distributed among resistant E. coli strains, with the most common plasmid replicon types being L/M and Y. Integrons were detected in 19% of E. coli isolates. RAPD analysis categorised the E. coli isolates into three clusters. MLST revealed seven different sequence types (STs), with ST10 being the most common. Conclusions: This study demonstrated a high prevalence of animals carrying potential ESBL- and AmpC-producing E. coli and emphasises the need for rigorous surveillance in the animal sector to identify critical control points conducive to prevent the rapid dissemination of AMR.